Answer:
The answer to the question is:
(F+G)(x)= x²+2x+2
Explanation:
The solution of the given question is pretty simple.
The given equations are
F(x) = 2x
G(x) = x²+2
We have to find (F+G)(x).
Which means that we simply have to add the values of both functions F(x) and G(x).
(F+G)(x) = F(x) + G(x)
All we have to do is substitute the values of both functions F(x) and G(x) into the given equation.
(F+G)(x) = (2x) + (x² +2)
Rearranging the terms
(F+G)(x)= x²+2x+2
Which is the answer to the question